Peserta Didik dengan Pengecualian (Exceptional Learner) - Siti Masitoh (Muaddib: Jurnal Pendidikan Agama Islam, 2024)
Exceptional learners are students with special educational needs, whether due to above-average intelligence or certain limitations. This article discusses the characteristics, needs, and effective teaching strategies for exceptional learners in Indonesia. Through an in-depth literature review, this article explores relevant educational psychology theories and pedagogical approaches that can be applied to meet the unique needs of these students. The results of this study indicate that understanding and implementing appropriate strategies can enhance the quality of learning and development of exceptional learners. This article also recommends the importance of specialized training for educators in managing exceptional learners to provide inclusive and equitable education.